The Influence of Sustainability Campaign Messages on “Pijak Bumi” Brand Image Through Price Perception - Arika, Linda Okti; Gracia, Amanda Bunga; Al Husain, A. Hasan (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2025)
This research aims to explore how sustainability campaign messages can influence the brand image of Pijak Bumi as an environmentally friendly brand, with price perception considered as a mediating variable. The theory employed in this study is the S-O-R (Stimulus-Organism-Response) theory, which explains how stimuli perceived by individuals can trigger responses, whether positive or negative, internally or externally. The research adopts a quantitative approach with an associative method. Based on its objectives and data type, this study falls into the descriptive category. The data analysis technique used is Partial Least Square-Structural Equation Modeling (PLS-SEM), enabling researchers to test complex relationships between variables. The study findings indicated that sustainability campaign messages significantly influence the brand image of Pijak Bumi as an environmentally friendly brand, with price perception acting as a mediator. The alternative hypothesis is accepted, while the null hypothesis is rejected, indicating that price perception plays a crucial role in reinforcing the impact of campaign messages on brand image. These findings provide valuable insights for marketers in designing effective communication strategies to enhance the promoted brand image.